2013
DOI: 10.1002/hed.23297
|View full text |Cite
|
Sign up to set email alerts
|

Tonsillar cancer: The Peter MacCallum experience with unilateral and bilateral irradiation

Abstract: These results support the potential use of unilateral radiation therapy (RT) for lateralized tonsil primaries even with advanced ipsilateral nodal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 9 publications
5
51
1
Order By: Relevance
“…Despite the common practice to restrict unilateral treatment for N0‐N1 ipsilateral nodal disease, the majority of unilateral series do incorporate varying proportions of patients with N2/N3 disease with more recent reports incorporating higher percentages. Patients with N2/3 disease comprised 16%‐17% in the series by O'Sullivan et al, Kagei et al, and Jackson et al; 27%‐33% in studies by Al‐Mamgani et al, Murthy and Hendrickson, and Liu et al; 42%‐65% by Chronowski et al; and, in the present series, such patients composed 96% of the study cohort reported by Cramer et al In the report by Cramer et al, 23 patients were treated with definitive unilateral concurrent chemoradiotherapy (Table ). All the patients were treated with IMRT and were T1‐T2 with N classifications as follows: N1 = 1 patient; N2a = 4 patients; and N2b = 18 patients.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Despite the common practice to restrict unilateral treatment for N0‐N1 ipsilateral nodal disease, the majority of unilateral series do incorporate varying proportions of patients with N2/N3 disease with more recent reports incorporating higher percentages. Patients with N2/3 disease comprised 16%‐17% in the series by O'Sullivan et al, Kagei et al, and Jackson et al; 27%‐33% in studies by Al‐Mamgani et al, Murthy and Hendrickson, and Liu et al; 42%‐65% by Chronowski et al; and, in the present series, such patients composed 96% of the study cohort reported by Cramer et al In the report by Cramer et al, 23 patients were treated with definitive unilateral concurrent chemoradiotherapy (Table ). All the patients were treated with IMRT and were T1‐T2 with N classifications as follows: N1 = 1 patient; N2a = 4 patients; and N2b = 18 patients.…”
Section: Discussionsupporting
confidence: 48%
“…Two of the most recent series define laterality as >1 cm from midline. Liu et al reported the Peter MacCallum Center experience of 58 patients treated unilaterally. Over 80% of the patients had documented lateralized disease defined as being >1 cm from midline.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently active research into treatment deintensification for HPV/p16‐positive oropharyngeal cancers; however, the role of deintensification by reduction in radiotherapy volumes tends to be overlooked. Our results for unilateral treatment of lateralized tonsil cancers and the results of this study suggest that unilateral radiotherapy would be safe, and clinically, it is an effective way to reduce acute and late treatment toxicities.…”
Section: Discussionmentioning
confidence: 56%
“…Patients who had a suspicious lesion in the base of tongue on examination or imaging were treated with bilateral neck radiotherapy despite negative biopsies. This treatment paradigm is in keeping with studies that have safely treated early oropharyngeal primaries with unilateral radiotherapy, which excluded known base of tongue involvement . Our series also excluded the outcomes of patients with isolated level IV, V, and parotid nodal disease, as they are likely to represent a different disease entity.…”
Section: Discussionmentioning
confidence: 82%
“…Significant controversy remains regarding the use of unilateral RT in some subgroups of patients with palatine tonsillar cancer, particularly in those with N2b neck disease. The 2011 American College of Radiology (ACR) Appropriateness Criteria recommended bilateral RT for this subgroup of patients, but some authors challenged this recommendation . In light of this controversy, we hypothesized that the location of the primary tumor was more important than the lymph node stage of the ipsilateral neck and the presence of extracapsular extension (ECE).…”
Section: Introductionmentioning
confidence: 99%